Spatio-temporal variation in Atlantic bluefin tuna (Thunnus thynnus) catch rates and sizes in a scientific catch-and-release fishery - Grace E. McNicholas; Catherine Waters; William K. Roche; Luke W.J. Cameron; Alan Drumm; Hugo Maxwell; Ciara M. Wögerbauer; Pat Mannix; Nicholas L. Payne (Fisheries Research, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Multifactor analysis of land use transitions in a drought-affected rice region - Luke A. Salvato; Cameron Pittelkow; Bruce A. Linquist (Field Crops Research, 2025)

Movements, growth rates and strong sexual segregation in critically endangered tope sharks Galeorhinus galeus in the Northeast Atlantic - Luke W. J. Cameron; Erin O. Jones; Paul J. Mensink; William K. Roche; Ciara Wögerbauer; Nicholas L. Payne (Journal of Fish Biology, 2025)
The tope ( Galeorhinus galeus , Linnaeus, 1758) is a critically endangered shark, which, like numerous elasmobranchs, faces severe global decline. There are, however, substantial disparities between this species' global conservation status and those of some local populations, with the Northeast Atlantic representing a relative stronghold for this species. However, several areas of uncertainty, particularly regarding individual movement patterns, currently hamper region‐specific conservation efforts. Therefore, utilising capture‐mark‐recapture tagging data, collected predominantly by recreational anglers in Ireland – but with recaptures throughout the Northeast Atlantic and Mediterranean – we investigated regional population structure, spatial segregation and individual movement patterns, and estimated sex‐specific individual growth rates. This revealed a marked pattern of sexual segregation, with females residing further south than males overall, and with an Irish‐specific trend towards male‐dominated catches in Atlantic regions versus more even sex ratios in the Irish and Celtic Seas. Recapture timings and locations suggest that female movements are more strongly driven by seasonal water temperatures changes, being broadly in line with the north–south migratory paradigm. Spatiotemporal overlap of mature individuals suggests that the North Channel, Irish Sea and northern Celtic Sea may constitute a key mating area. Female sharks may utilise southerly regions during gestation, with the presence of young‐of‐the‐year indicating that the Irish Sea and neighbouring regions subsequently act as parturition/nursery areas. Our results demonstrate the value of such long‐term programmes, in this case facilitated by citizen science, in identifying broad‐scale movement patterns in wide‐ranging species and specific regions of interest for further study and/or implementation of targeted conservation measures.

Review of plant cellulose-based aerogel materials for oil/water mixture separation - Yitong Zhai; Xiaowen Yuan; Cameron C. Weber; Russell J. Varley; Luke C. Henderson (Journal of Environmental Chemical Engineering, 2024)

Investigating the influences of precipitation, snowmelt, and freeze-thaw on rockfall in Glenwood Canyon, Colorado using terrestrial laser scanning - Luke Weidner; Gabriel Walton; Cameron Phillips (Landslides, 2024)

Consumer purchase response to e-bike incentives: Results from a nationwide stated preference study - Luke R. Jones; Cameron Bennett; John H. MacArthur; Christopher R. Cherry (Transportation Research Part D: Transport and Environment, 2024)

A geospatial assessment of soil properties to identify the potential for crop rotation in rice systems - Luke A. Salvato; Cameron M. Pittelkow; Anthony T. O’Geen; Bruce A. Linquist (Agriculture, Ecosystems & Environment, 2024)

Northerly range expansion and first confirmed records of the smalltooth sand tiger shark, Odontaspis ferox , in the United Kingdom and Ireland - David J. Curnick; Rob Deaville; Jenny R. Bortoluzzi; Luke Cameron; Jeanette E. L. Carlsson; Jens Carlsson; Haley R. Dolton; Cat A. Gordon; Phil Hosegood; Alicia Nilsson; Matthew W. Perkins; Kevin J. Purves; et al. (Journal of Fish Biology, 2023)
Three Odontaspis ferox (confirmed by mtDNA barcoding) were found in the English Channel and Celtic Sea in 2023 at Lepe, UK (50.7846, −1.3508), Kilmore Quay, Ireland (52.1714, −6.5937), and Lyme Bay, UK (50.6448, −2.9302). These are the first records of O. ferox in either country, and extend the species' range by over three degrees of latitude, to >52° N. They were ~275 (female), 433 (female), and 293 cm (male) total length, respectively. These continue a series of new records, possibly indicative of a climate change−induced shift in the species' range.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Long‐term change in the avifauna of undisturbed Amazonian rainforest: ground‐foraging birds disappear and the baseline shifts - Philip C Stouffer; Vitek Jirinec; Cameron L. Rutt; Richard O. Bierregaard; Angélica Hernández‐Palma; Erik I. Johnson; Stephen R. Midway; Luke L. Powell; Jared D. Wolfe; Thomas E. Lovejoy (Ecology Letters, 2021)
How are rainforest birds faring in the Anthropocene? We use bird captures spanning > 35 years from 55 sites within a vast area of intact Amazonian rainforest to reveal reduced abundance of terrestrial and near‐ground insectivores in the absence of deforestation, edge effects or other direct anthropogenic landscape change. Because undisturbed forest includes far fewer terrestrial and near‐ground insectivores than it did historically, today’s fragments and second growth are more impoverished than shown by comparisons with modern ‘control’ sites. Any goals for bird community recovery in Amazonian second growth should recognise that a modern bird community will inevitably differ from a baseline from > 35 years ago. Abundance patterns driven by landscape change may be the most conspicuous manifestation of human activity, but biodiversity declines in undisturbed forest represent hidden losses, possibly driven by climate change, that may be pervasive in intact Amazonian forests and other systems considered to be undisturbed.

Did geckos ride the Palawan raft to the Philippines? - Cameron D. Siler; Jamie R. Oaks; Luke J. Welton; Charles W. Linkem; John C. Swab; Arvin C. Diesmos; Rafe M. Brown (Journal of Biogeography, 2012)
Aim We examine the genetic diversity within the lizard genus Gekko in the Philippine islands to understand the role of geography and geological history in shaping species diversity in this group. We test multiple biogeographical hypotheses of species relationships, including the recently proposed Palawan Ark Hypothesis. Location Southeast Asia and the Philippines. Methods Samples of all island endemic and widespread Philippine Gekko species were collected and sequenced for one mitochondrial gene (NADH dehydrogenase subunit 2) and one nuclear gene (phosducin). We used maximum likelihood and Bayesian phylogenetic methods to derive the phylogeny. Divergence time analyses were used to estimate the time tree of Philippine Gekko in order to test biogeographical predictions of species relationships. The phylogenetic trees from the posterior distribution of the Bayesian analyses were used for testing biogeographical hypotheses. Haplotype networks were created for the widespread species Gekko mindorensis to explore genetic variation within recently divergent clades. Results Both maximum likelihood and Bayesian phylogenetic analyses indicated that Philippine Gekko species are a diverse clade with a long history in the archipelago. Ancestral range reconstruction and divergence time analyses suggest a Palawan microcontinental origin for this clade, coinciding with Palawan’s separation from Asia beginning 30 Ma, with subsequent diversification in the oceanic Philippine islands. The widespread species G. mindorensis and G. monarchus diversified in the late Miocene/early Pliocene and are potentially complexes of numerous undescribed species. Main conclusions The view of the Philippine islands as a ‘fringing archipelago’ does not explain the pattern of species diversity in the genus Gekko . Philippine Gekko species have diversified within the archipelago over millions of years of isolation, forming a large diverse group of endemic species. Furthermore, the Philippine radiation of gekkonid lizards demonstrates biogeographical patterns most consistent with stochastic colonization followed by in situ diversification. Our results reveal the need to consider deeper time geological processes and their potential role in the evolution of some Philippine terrestrial organisms.

Remarkable Amphibian Biomass and Abundance in an Isolated Wetland: Implications for Wetland Conservation - J. WHITFIELD GIBBONS; CHRISTOPHER T. WINNE; DAVID E. SCOTT; JOHN D. WILLSON; XAVIER GLAUDAS; KIMBERLY M. ANDREWS; BRIAN D. TODD; LUKE A. FEDEWA; LUCAS WILKINSON; RIA N. TSALIAGOS; STEVEN J. HARPER; JUDITH L. GREENE; et al. (Conservation Biology, 2006)
Despite the continuing loss of wetland habitats and associated declines in amphibian populations, attempts to translate wetland losses into measurable losses to ecosystems have been lacking. We estimated the potential productivity from the amphibian community that would be compromised by the loss of a single isolated wetland that has been protected from most industrial, agricultural, and urban impacts for the past 54 years. We used a continuous drift fence at Ellenton Bay, a 10‐ha freshwater wetland on the Savannah River Site, near Aiken, South Carolina (U.S.A.), to sample all amphibians for 1 year following a prolonged drought. Despite intensive agricultural use of the land surrounding Ellenton Bay prior to 1951, we documented 24 species and remarkably high numbers and biomass of juvenile amphibians (>360,000 individuals; >1,400 kg) produced during one breeding season. Anurans (17 species) were more abundant than salamanders (7 species), comprising 96.4% of individual captures. Most (95.9%) of the amphibian biomass came from 232095 individuals of a single species of anuran (southern leopard frog [Rana sphenocephala ]). Our results revealed the resilience of an amphibian community to natural stressors and historical habitat alteration and the potential magnitude of biomass and energy transfer from isolated wetlands to surrounding terrestrial habitat. We attributed the postdrought success of amphibians to a combination of adult longevity (often >5 years), a reduction in predator abundance, and an abundance of larval food resources. Likewise, the increase of forest cover around Ellenton Bay from 60% in 2001 probably contributed to the long‐term persistence of amphibians at this site. Our findings provide an optimistic counterpoint to the issue of the global decline of biological diversity by demonstrating that conservation efforts can mitigate historical habitat degradation.